The Attraction of Cultural Tourism from a Creativepreneurship Perspective - Vanna Nazwa Durrani; Puti Intan Al Chaniago; Nadya Sagita Junaedi; Senny Luckyardi (IJSM, 2026)
Bandung is one of the creative economy centers in Indonesia with great potential in cultural tourism. This study aims to analyze the cultural appeal and the influence of cultural elements and the application of creativepreneurship principles on tourist interest and satisfaction. This study also evaluates the economic impact of the gallery on the local community and provides recommendations for development. The study uses a case study method at the NuArt Gallery with a qualitative descriptive approach with data collection techniques through observation, interviews with visitors to the NuArt Gallery, and documentation studies. Data were analyzed thematically to explore the meaning, experience, and perception of cultural values and gallery management strategies. Initial results indicate that the monumental sculpture collection and open art space are the main attractions. Positive responses from visitors indicate that activities such as workshops and collaborations with local artists support the concept of creativepreneurship and increase satisfaction. The NuArt Gallery is expected to have a positive economic impact on the surrounding community through increased income and tourist visits. Initial conclusions indicate that the NuArt Gallery has great potential as a cultural tourism destination and a driver of the creative economy in Bandung. The findings show a positive trend.